2003
DOI: 10.1046/j.1365-313x.2003.01790.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of AtHMA4, a P1B‐type ATPase of the Zn/Co/Cd/Pb subclass

Abstract: SummaryMechanisms are required by all organisms to maintain the concentration of essential heavy metals (e.g. Zn and Cu) within physiological limits and to minimise the detrimental effects of non-essential heavy metals (e.g. Cd). Heavy-metal P-type ATPases (HMAs) are a subgroup of the P-type ATPase superfamily that may contribute to metal homeostasis in plants. We cloned and characterised a member of this family, AtHMA4, from Arabidopsis thaliana that clusters with the Zn/Co/Cd/Pb subclass of HMAs on phylogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
186
1
5

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 220 publications
(203 citation statements)
references
References 50 publications
(77 reference statements)
8
186
1
5
Order By: Relevance
“…5). This response to increasing plant Cd status in T. caerulescens is quite different than what has been reported for its homolog in Arabidopsis, where it has been shown that root expression of AtHMA4 is down-regulated by plant exposure to Cd (Mills et al, 2003).…”
Section: Tissue-specific Expression Of Tchma4 In T Caerulescenscontrasting
confidence: 87%
See 4 more Smart Citations
“…5). This response to increasing plant Cd status in T. caerulescens is quite different than what has been reported for its homolog in Arabidopsis, where it has been shown that root expression of AtHMA4 is down-regulated by plant exposure to Cd (Mills et al, 2003).…”
Section: Tissue-specific Expression Of Tchma4 In T Caerulescenscontrasting
confidence: 87%
“…Here we present evidence that this ATPase facilitates a high degree of heavy metal tolerance in yeast by mediating the active efflux of heavy metals out of the cell. However in T. caerulescens, based on differences in tissue-specific and metal-responsive expression of this transporter compared with expression of its homolog in Arabidopsis (Arabidopsis thaliana; Mills et al, 2003;Hussain et al, 2004), we suggest that it may not be involved in metal tolerance in Thlaspi. Instead, we propose that it may play a role in xylem loading of metals and thus could be a key player in the hyperaccumulation phenotype expressed in T. caerulescens.…”
mentioning
confidence: 81%
See 3 more Smart Citations